The management of change & copyright - Duffy, J.S. (1985)
The main focus of this thesis is the three copyright collecting societies operating in the music field - PRS, which looks after the public performance and broadcasting rights in music, MCPS which is responsible for the mechanical (recording) right in music and PPL which looks after the public performance and broadcasting rights in sound recordings. Between them, these three societies had gross revenue (before costs) of over £83 million in 1983, of which PRS was responsible for 72%, MCPS for 17% and PPL for 11%. The thesis attempts to investigate their operations and performance. In many ways they are similar but there are also important differences especially between PRS and PPL on the one hand and MCPS on the other. They all depend for their operations on the concept of collective licensing – that copyright owners can more effectively exploit their copyrights by banding together in societies such as PRS, MCPS and PPL. In many cases, collective licensing represents the only possibility for the copyright owner to receive income from his copyright. All three societies also use blanket licences in their operations to various extents this means that licensees can use the entire repertoire of the society on payment of royalties and provided they supply the society with returns of their music use (on which the society bases distributions to members). Since PRS and PPL are effective monopolies, representing virtually all copyright owners in their respective fields, such licensing can be effective. MCPS is an effective monopoly only in the broadcasting field and it is only in this field that it employs blanket licensing. The other fundamental differences between MCPS and the other two societies are its agency relationship with its members and its charging of a commission to cover costs. All of this is looked at in detail.